(untitled) (Bangladesh Medical Journal, 2016)
Incidence of obesity among postmenopausal women is increasing throughout the world, leading to life threatening medical problem like cardiovascular diseases, type 2 diabetes mellitus. Estrogen deficiency that develops during menopause is likely the etiological factors for development of abdominal obesity. Increased incidence of cardiovascular diseases in postmenopausal women may be due to abdominal obesity caused by lower level of estrogen hormone. The study was carried out to observe the association of obesity with serum estrogen level in postmenopausal women. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of 90 female subjects were selected from different areas of Dhaka city. Among them, 60 postmenopausal women with age ranging from 50 to 60 years were taken as study group and 30 apparently healthy premenopausal women with age ranging from 20 to 30 years were included as control group for comparison. Waist circumference was measured and body mass index (BMI) was calculated in both groups. Serum estrogen level was estimated in order to assess the hormonal level of postmenopausal women. The value of waist circumference was higher in postmenopausal women than those of premenopausal women and result was statistically non significant. Body mass index value was significantly (p<0.001) higher in postmenopausal women in comparison to those of premenopausal women. In postmenopausal women serum estrogen level was lower than premenopausal women and serum estrogen level showed negative correlation with waist circumference and body mass index values. All these correlations were statistically non significant. Present study revealed that there is association of obesity with serum estrogen level in postmenopausal women. Bangladesh Med J. 2016 May; 45 (2): 79-84